2016
DOI: 10.17219/acem/34654
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Carotid Arterial Stiffness and Left Ventricular Concentric Hypertrophy in Hypertension

Abstract: al and functional arterial changes contribute to the pathophysiology of LVH. One concept is that arterial remodeling might parallel left ventricular (LV) remodeling due to pressure overload and additional non-hemodynamic factors in hypertension [2]. This phenomenon might have an impact on the inAssessment of both left ventricular hypertrophy (LVH) and abnormal structure and function of the conduit arteries as features of the target organ damage (TOD) is crucial in the risk stratification and management of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 26 publications
0
19
0
3
Order By: Relevance
“…[2][3][4]9 Hypertension is multifactorial, but has been related to vascular wall thickness and stiffness, and leads to atherosclerosis. 10 However, in most of these studies, hypertension was more strongly related to fibroid cases that led to hysterectomy rather than fibroid cases detected before needing surgical intervention. 4,8,9 We aimed to study the association between fibroids and CVD using markers of subclinical disease to further elucidate possible common pathways: (1) wall thickness and vascular stiffness using markers of carotid intima media thickness (CIMT) and left ventricular (LV) mass and (2) plaque formation using coronary artery calcification (CAC).…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4]9 Hypertension is multifactorial, but has been related to vascular wall thickness and stiffness, and leads to atherosclerosis. 10 However, in most of these studies, hypertension was more strongly related to fibroid cases that led to hysterectomy rather than fibroid cases detected before needing surgical intervention. 4,8,9 We aimed to study the association between fibroids and CVD using markers of subclinical disease to further elucidate possible common pathways: (1) wall thickness and vascular stiffness using markers of carotid intima media thickness (CIMT) and left ventricular (LV) mass and (2) plaque formation using coronary artery calcification (CAC).…”
Section: Introductionmentioning
confidence: 98%
“…Carotid elasticity and distensibility are two important parameters that can be easily evaluated by ultrasonography and show subclinical atherosclerosis. The role of both elasticity and distensibility in predicting cardiovascular adverse events has been demonstrated in previous studies [5][6][7] .…”
Section: Introductionmentioning
confidence: 76%
“…18 Brouwer et al in LTSCC even found a negative association between carotid IMT and treatment with anthracyclines, both as categorical variables [yes/no] and per 100mg/m2 cumulative dose. 22 Further, Bowers et al observed no association between ChT and the risk of stroke in patients treated for HD in childhood. 5 To our knowledge, only one study dealing with LTSCC suggested that anthracyclines causes impaired endothelial function, which is early event in atherogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…PWV, the one-point pulse wave velocity (m/s), is calculated from the time delay between two adjacent distension waveforms from water hammer equation with the use of the β stiffness parameter 22 :…”
Section: Carotid Measurementsmentioning
confidence: 99%